Unveiling the Narratives of English Master Students Navigating AI in Scientific Writing - Endah Yulia Rahayu (Journal of Applied Linguistics and English Education, 2023)
The study employs a narrative inquiry approach and involves five English master students who have used AI tools in their academic writing. The participants' experiences and opinions on AI's role in scientific writing are analysed through thematic analysis. The findings of the study reveal that master students perceive AI as a helpful tool that can assist in various aspects of scientific writing, such as brainstorming ideas, the writing process itself, and refining scientific papers. AI tools have transformed the pre-writing process by offering solutions to streamline the workflow and unlock new research paths. The students reported using AI tools for literature exploration and idea generation, refining arguments and style, boosting research efficiency, and visualizing data and findings. The study also highlights the importance of maintaining academic integrity and ensuring the originality of works when using AI-generated content, particularly pre-, during-, and post-writing processes. This study provides insights into the experiences of English master students in using AI tools for scientific writing and highlights the benefits and potential of using AI-based tools in scientific writing by English master students to improve their writing skills, streamline the writing process, and improve the overall quality of their scientific work.